PENERAPAN PENUGASAN MULTI-OBJECTIVE UNTUK MENGOPTIMALKAN BIAYA, WAKTU DAN KUALITAS MENGGUNAKAN METODE HUNGARIAN - Sri Basriati; Elfira Safitri; Muhammad Rizki (MAp (Mathematics and Applications) Journal, 2023)
Various problems be facing by the company to get optimal results. One of them in this research is to optimize cost, time and quality simultaneous to get a minimal solution. The optimization of these problems uses the Hungarian method by applying multi-objective assignments. Based on the of the optimal solution results from one-objective, two-objective and three-objective assignments, these third-objective assignment is the best result. So that in the case example, the optimal solution is obtaining where the total cost incurred is Rp. 24,950,000. The total time required is 96 days. While the quality of the rattan flower vase is very good, the decorative lighting is very good and the mat is very good, the shelf is very good, the table is very good, the wardrobe is very good and the guest chair is very good.